(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and aim: Hyperbilirubinemia is an elevation of the bilirubin levels in blood of newborn babiesthat presented as jaundice. This study aimed to evaluate the levels of important of immunological systemproteins (IgG, IgM, IgA, C3 and C4) in both newborn babies with severe hyperbilirubinemia and healthycontrols.Methods: Thirty (30) full-term neonates with severe hyperbilirubinemia (serum bilirubin >20 mg/dl) andtwenty five (25) healthy control full-term neonates were included in the study. Blood samples taken and Hb,total serum bilirubin, total protein measured immediately by spectrophotometer. IgG, IgM, IgA, C3 and C4measured by immune-nephelometric method.Results: In hyperbilirubinemia group (Male/ Female percentages) were (63% / 37%), (IgG 373.4±218 mg/dl),( IgM 20.5 ± 24.03 mg/dl), and (C3 209.4±17.81 mg/d)l values were significantly lower than controlgroup ( 588.2±298.5 mg/dl IgG, 26.44 ± 2.92 mg/dl IgM and 627.5±221.1 mg/dl for C3). Correlationanalysis revealed that in control group IgG, IgM, and C3 shown to be significantly (P value <0.05) andpositively correlated (r-value > 3) with both age and weight.Conclusions: jaundice is a risk factor for sepsis that could be due to lower levels of immunoglobulins andcomplements components. The normal development of immune system that observed with increasing ageand weight was impaired in patients with neonatal hyperbilirubinemia.